KOMUNIKASI INTERPERSONAL ANTARA MANAJER DAN KARYAWAN DALAM MENJAGA KUALITAS PELAYANAN PELANGGAN PADA CAFE KOPI CENDANA KOTA SURAKARTA - Cahya Fahrurozi, Anindhita; Suryo, Herning; Siswanto, Siswanto (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
ABSTRACT Communication process in organisation is very important to measure employee performance. In Cendana Coffee Cafe Surakarta City, managers play an important role in interpersonal communication to maintain service quality. The result is an increase in visitors but there are also criticisms related to communication and employee motivation. This research focuses on describing interpersonal communication between managers and employees in maintaining service quality at Cendana Coffee Cafe Surakarta City. The type of research used is descriptive qualitative. The data sources in this research are primary data sources and secondary data sources. The data collection technique used in this research is interview, observation, documentation. The results showed that interpersonal communication between managers and employees at the Cendana Coffee cafe in Surakarta City was carried out by verbal and nonverbal communication. Verbal communication such as face-to-face conversations and briefings, while nonverbal communication through body language and facial expressions when serving customers. In carrying out interpersonal communication, it is carried out by carrying out 4 (four) indicators, namely openness, empathy, mutual support, equality. While the positive attitude indicator has not been running in the manager's interpersonal communication with employees. Keywords: Interpersonal Communication, Service Quality, Cendana Coffee